IMPLEMENTASI MODEL PEMBELAJARAN PASPOR (PAIRING, SQUARE, PRESENTATION, REPETITION) UNTUK MENINGKATKAN KETERAMPILAN KOLABORATIF SISWA KELAS X TKJ SMK NEGERI 1 RAMBAH - Nindi Bunga Iqnas Bunga; Jufri Jufri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the PASPOR learning model (Pairing, Square, Presentation, Repetition) on students' collaborative skills. This research uses a quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design. The population of this study was all students of class X TKJ at SMK Negeri 1 Rambah, with two classes selected as samples, namely the experimental class and the control class. Data were collected through observation, questionnaires, and pretest-posttest. Data analysis techniques included normality test (Shapiro-Wilk), Mann–Whitney test, N-Gain, and effect size. The results showed that the application of the PASPOR model had a significant effect on improving students' collaborative skills. The N-Gain results indicated a moderate improvement, and the effect size showed a strong influence. Thus, the PASPOR model is effective in enhancing collaborative skills in vocational high school students.